2013
DOI: 10.1186/1471-2407-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Early onset recall pneumonitis during targeted therapy with sunitinib

Abstract: BackgroundSunitinib interacts with radiation therapy, leading to synergism of the toxicities of these treatments. Radiation recall pneumonitis is a rare but serious complication of targeted therapy with tyrosine kinase inhibitors.Case presentationThe case of a patient with metastatic renal cell cancer (RCC) who developed recall pneumonitis on the first cycle of systemic sunitinib treatment is reported here. A 65-year-old man with RCC and bone metastasis underwent radiation therapy on his thoracic vertebrae (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Although there are reports of radiation dermatitis, bowel toxicities, and pneumonitis, TKIs are generally well tolerated when delivered with radiation. 2,5,8,18,29 However, the safety and efficacy of concur-rent therapy remains particularly unknown despite a growing utilization of SRS in the mRCC patient population. Several investigators have postulated that TKIs offer an added benefit when delivered concurrently with radiation, extrapolating from preclinical models and the radiobiology of SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reports of radiation dermatitis, bowel toxicities, and pneumonitis, TKIs are generally well tolerated when delivered with radiation. 2,5,8,18,29 However, the safety and efficacy of concur-rent therapy remains particularly unknown despite a growing utilization of SRS in the mRCC patient population. Several investigators have postulated that TKIs offer an added benefit when delivered concurrently with radiation, extrapolating from preclinical models and the radiobiology of SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Although interstitial pneumonia was an infrequent occurrence and relatively mild in severity, the phase 1 trial concluded that the combination of the mTOR inhibitor and sunitinib produced a high degree of toxicity requiring dose attenuation of both drugs. In addition, there have been two case reports of radiation‐induced interstitial pneumonia as a recall phenomenon occurring during systemic treatment with sunitinib . Taken together, these findings suggest that the systemic administration of mTOR inhibitors and radiation therapy subclinically induces local and/or diffuse lung damage, which can lead to toxic synergism with sunitinib.…”
Section: Discussionmentioning
confidence: 89%
“…There is only one report of sorafenib‐induced interstitial pneumonia, and no reports of pazopanib‐induced pneumonia. In addition, there are just three reports of sunitinib‐induced interstitial pneumonia, and no reports thus far of sunitinib‐induced interstitial pneumonia after recovery from temsirolimus‐induced interstitial pneumonia. In a phase 1 trial of the mTOR inhibitor, everolimus plus sunitinib, in patients with metastatic RCC, one case (equivalent 5%) of grade 2 interstitial pneumonia was reported .…”
Section: Discussionmentioning
confidence: 99%
“…The literature search identified 1440 unique results, where 47 articles met the inclusion criteria with a total of 807 patients included in the data analysis ( Figure 1 ). 1 , 10 , 11 , 13 , 15 , 18 – 60 Demographics, presenting features, treatment, and survival information were compiled for those patients with known status. The majority of patients were male (75.5%), and the mean age at diagnosis of RCC spine metastasis was 56.7 years.…”
Section: Resultsmentioning
confidence: 99%